Mental and Emotional Changes in the Elderly: A Literature Review - Balqis Prudena Kurnia Pambudi; Cantika Brilliant Senna; Muhammad Rafly Adrian Sugiono; Agustine Mahardika (Medical and Health Journal, 2026)
Emotional and mental changes in the elderly represent a psychological adaptation process that occurs with aging, encompassing shifts in thinking, emotional responses, and social interactions. A deeper understanding of this topic is essential for designing effective interventions aimed at improving the quality of life of older adults. Elderly individuals are vulnerable to experiencing issues such as excessive anxiety, profound sadness, loneliness, guilt, and decreased self-esteem. These conditions may be triggered by internal factors, including neurobiological changes and chronic stress, as well as external factors, such as age discrimination and social isolation. Such changes significantly impact various dimensions of the elderly’s quality of life, including physical, psychological, social, and spiritual aspects. Therefore, a holistic approach that involves the active role of the family in providing emotional and social support is crucial. Non-pharmacological interventions, such as cognitive behavioral therapy (CBT), meditation, and physical activity, have been proven effective in preventing and managing mental health problems in older adults and in promoting overall well-being.